Alendronate/Vitamin D for attenuating bone mineral density loss during antiretroviral initiation: a pilot randomized controlled trial. Issue 6 (2nd November 2019) - Tan, Darrell H. S.; Lee, Terry; Raboud, Janet; Qamar, Attia; Cheung, Angela M.; Walmsley, Sharon
Abstract : Background: Antiretroviral therapy (ART) initiation is associated with decreases in bone mineral density (BMD). Objectives: To plan for a larger trial, we sought to obtain preliminary estimates for the difference in the change in BMD at 48 weeks achieved with 24 weeks of prophylactic alendronate/vitamin D during ART initiation compared to no intervention, the within-group standard deviation of this change, and intra-patient correlation coefficient for repeated BMDs. Secondary objectives included assessing enrollment feasibility, treatment acceptability, adherence and safety. Methods: We randomized treatment-naïve HIV-positive adults initiating tenofovir disoproxil fumarate/emtricitabine/elvitegravir/cobicistat or abacavir/lamivudine/dolutegravir 1:1:1 to immediate alendronate/vitamin D3 70 mg/5600 IU for 24 weeks (concomitant treatment arm, CTA), the same intervention starting 24 weeks after study entry (delayed treatment arm, DTA), or no bone anti-resorptive therapy (standard of care, SOC). We assessed BMD, acceptability, adverse events and drug adherence at baseline, week 24 and week 48. Results: Of 29 included participants, 72% initiated TDF/FTC/ELV/c and 28% initiated ABC/3TC/DTG. Median (IQR) CD4 count was 388 (303, 525) cells/mm 3 and median plasma HIV RNA was 4.45 (2.26, 4.84) log10 copies/mL. The mean (SD) percentage change in BMD for the CTA and DTA combined was 1.95% (2.53%), 0.38% (3.34%), and −0.57% (3.50%) at the lumbar spine, femoral neck and total hip respectively at 48 weeks. The ICC among repeated measurements of BMD was 0.978, 0.964, and 0.967 at these sites, respectively. Enrollment feasibility, drug acceptability, adherence, and tolerability were good. Conclusions: Our findings inform the sample size for a larger trial of bone anti-resorptive therapy during ART initiation and support feasibility.